2015
DOI: 10.1080/21683603.2015.1064841
|View full text |Cite
|
Sign up to set email alerts
|

Know How to Teach Me… Evaluating the Effects of an In-Service Training Program for Regular School Teachers Toward Inclusive Education

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
1
18
0
9
Order By: Relevance
“…As most of these children were in lower age group, it is expected many of these to be staying at home, but the numbers of ASDs cases in special school or regular school were low. Although international and national organizations are increasingly advocating inclusive education for students with disabilities globally, but in many countries including India these children do not even attend schools, let alone a special one [58][59][60][61]. In developing countries including India, the implementation of inclusive education of children with disabilities including ASDs is basically undertaken by the non-government organizations (NGOs) instead of a country's government [62].…”
Section: Discussionmentioning
confidence: 99%
“…As most of these children were in lower age group, it is expected many of these to be staying at home, but the numbers of ASDs cases in special school or regular school were low. Although international and national organizations are increasingly advocating inclusive education for students with disabilities globally, but in many countries including India these children do not even attend schools, let alone a special one [58][59][60][61]. In developing countries including India, the implementation of inclusive education of children with disabilities including ASDs is basically undertaken by the non-government organizations (NGOs) instead of a country's government [62].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this literature review, most teachers appeared to have positive views and attitudes towards the integration of students with autism (Cassimos et al, 2013;Humphrey & Symes, 2011;Park & Chitiyo, 2011;Segall, 2008;Srivastava et al, 2015b) and used effective classroom management techniques, such as providing more time for task completion, placement of students at the front of the class, but also involvement of students in discussions (Lodhi et al, 2016). Teachers generally demonstrated positive expectations on the education of students with autism (Rodriguez et al, 2012).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…Their knowledge about disabilities, however, was low, but knowledge about inclusive teaching methods was acceptable, which was a significant finding. Srivastava, De Boer, and Pijl (2015b) examined the knowledge and attitudes of 79 regular primary school teachers from Jaipur city, India. The outcomes revealed that despite initial neutral attitudes in both groups, the experimental group had significantly more positive attitudes and had increased their knowledge about dyslexia, intellectual disability, ASD, and teaching methods.…”
Section: Malaysiamentioning
confidence: 99%
“…Before the training program was conducted, the researchers observed some classes and interviewed the teachers to ascertain the need areas. Subsequently, the training was designed on the basis of the results of the need analysis and by consulting the designs of similar training programs conducted by Srivastava, De Boer and Pijl (2015), and Kurniawati et al (2016). Some other scholarly literature was also used as reference for teaching strategies for inclusive classrooms.…”
Section: Serasi Training Programmentioning
confidence: 99%
“…However, that particular study evinced some limitations. Kurniawati et al (2016) and Srivastava et al (2015), found, on the contrary, that teachers who participated in a training program became more knowledgeable about students with SEN and about inclusive schooling. These studies found that the cognitiveaffective components of the attitudes of such teachers also improved significantly.…”
Section: Introductionmentioning
confidence: 95%